A nanocomposite of dual-phase Fe/TiCN wrapped in nitrogen-doped carbon with magnetic and dielectric characters for superior microwave absorption. Issue 8 (15th April 2023) - Wang, Dongxing; Javid, Muhammad; Saleem, Muhammad Farooq; Wu, Min; Shi, Yuli; Rauf, Abdul; Xu, Xiaohui; Dong, Xinglong
Abstract: A careful approach to the optimization of magnetic and dielectric losses in nanomaterials can improve the electromagnetic wave absorption loss performance for certain microwave absorption applications. In this study we prepared dual core (Fe/TiCN) coated with nitrogen (N) doped carbon shell nanocomposite by arc-discharge method under mix atmospheres of working gases and with varying elemental compositions. Among all nanocomposites, (Fe/TiC0.7 N0.3 )@N–C dual-core@ N- doped shell nanocomposite exhibits enhanced microwave absorption. Owing to the novel dual-core@ N-doped shell structure and numerous defects induced by doping N in carbon shells, an improved dielectric relaxation in composite is observed and the minimum reflection loss was reached −44.36 dB at 5.3 GHz for 4.8 mm thickness.